Efficient Three-Dimensional Simulation of Ultrasound Imaging Using a Parallel K -Space Method - Daoud, Mohammad I.; Lacefield, James C. (CMBES Proceedings, 2008)
Three-dimensional (3-D) simulations of ultrasound image formation can be used to investigate quantita- tive relationships between characteristics of ultrasound images and the microscopic structure of tissue, which can improve tissue characterization methods. However, such simulations involve high computational complexity which limits their use in imaging research. A parallel 3-D ultrasound simulator is presented that uses an ef- ficient numerical method to compute acoustic propaga- tion. The simulator runs on computer clusters and en- ables accurate 3-D simulations with short running times. Ultrasound images of a tissue-mimicking phantom cre- ated using the simulator show realistic 3-D refraction ar- tifacts. The parallel execution time of a simulated image using 20 cluster nodes was 18.61 hours compared to a serial execution time of 357.50 hours.